2016
DOI: 10.3892/ol.2016.5139
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-24 increases the sensitivity to paclitaxel in drug-resistant breast carcinoma cell lines via targeting ABCB9

Abstract: Paclitaxel has been widely used in the treatment of breast cancer. However, the development of drug resistance often increases the failure of chemotherapy. Growing evidence has reported the significant role of microRNAs (miRs) in drug resistance. The present study identified that miR-24 was significantly downregulated in paclitaxel-resistant (PR) breast cancer patients and in MCF-7/PR human breast carcinoma cells, and that overexpression of miR-24 could increase the effect of paclitaxel on drug-resistant breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
(42 reference statements)
0
26
0
Order By: Relevance
“…Conversely, no transcripts corresponding to resistance proteins were found to be higher in the NED group. We found that ABCA3 and ABCB9 transcripts were upregulated in the poor responders, and these transporters are specifically related to platinum and taxane accumulation (32)(33)(34). Taken together, these accumulation and transcript data suggest that AXL expression is associated with markers of chemoresistance.…”
Section: Axl Inhibition Affects Carboplatin Accumulation and Gene Expmentioning
confidence: 62%
“…Conversely, no transcripts corresponding to resistance proteins were found to be higher in the NED group. We found that ABCA3 and ABCB9 transcripts were upregulated in the poor responders, and these transporters are specifically related to platinum and taxane accumulation (32)(33)(34). Taken together, these accumulation and transcript data suggest that AXL expression is associated with markers of chemoresistance.…”
Section: Axl Inhibition Affects Carboplatin Accumulation and Gene Expmentioning
confidence: 62%
“…Conversely, miR-125b overexpression suppressed the EMT by Sema4C in PTX-resistant BC cells [21]. In addition, upregulation of miR-24 and miR-125b sensitized PTX-resistant BC cells to PTX [21,22]. MiR-451 also influenced the drug resistance of PTX-resistant BC cells by enhancing cell apoptosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although early diagnosis, radical surgery and the development of adjuvant therapy have improved the prognosis of breast cancer patients, this disease remains a major problem worldwide [3]. For the treatment of breast cancer, chemotherapy is one of the most important approaches currently [4-6]. Doxorubicin (dox) and paclitaxel (pax) have been used as available anti-cancer agents to treat tumours [7], including breast cancer [8].…”
Section: Introductionmentioning
confidence: 99%